2011
DOI: 10.1002/lary.21788
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depressive symptoms and initial quality of life and function in head and neck cancer

Abstract: Patients with HNCA have a high incidence of depressive symptoms at diagnosis, which is significantly higher in black patients, and is associated with poorer QOL and MDADI scores. Pretreatment depression may serve as a marker for patients with increased risk of swallowing impairment and reduced QOL who would benefit from targeted intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
2
33
3
Order By: Relevance
“…In a study of HNC patients with (versus without) persistent posttreament depressive symptomatology (i.e., patients with consistently elevated BDI scores for six months or more beyond the conclusion of treatment), Karnell and colleagues (2006) reported that patients experiencing persistent depressive affect were more likely to report worse HNC-specific HRQOL outcomes after adjusting for various clinical characteristics. Similar results have been found in other studies measuring depressive symptomatology and/or more general distress in HNC patients (e.g., Bornbaum, Fung, Franklin, Nichols, Yoo, & Doyle, 2011; Chan, Lua, Starmer, Sun, Rosenblatt, & Gourin, 2011; de Leeuw, de Graeff, Ros, Blijham, Hordijk, & Winnubst, 2000a). …”
Section: Psychological Factors In Hncsupporting
confidence: 91%
“…In a study of HNC patients with (versus without) persistent posttreament depressive symptomatology (i.e., patients with consistently elevated BDI scores for six months or more beyond the conclusion of treatment), Karnell and colleagues (2006) reported that patients experiencing persistent depressive affect were more likely to report worse HNC-specific HRQOL outcomes after adjusting for various clinical characteristics. Similar results have been found in other studies measuring depressive symptomatology and/or more general distress in HNC patients (e.g., Bornbaum, Fung, Franklin, Nichols, Yoo, & Doyle, 2011; Chan, Lua, Starmer, Sun, Rosenblatt, & Gourin, 2011; de Leeuw, de Graeff, Ros, Blijham, Hordijk, & Winnubst, 2000a). …”
Section: Psychological Factors In Hncsupporting
confidence: 91%
“…31–37 They are also behavioral factors associated with poorer HRQOL. 38,39 In our cohort, only 2% of African Americans never smoked, compared to approximately 21% of non-Hispanic whites who never smoked. At the time of the survey, we found equal percentages (26%) of current smokers; however, 46% of African Americans recently quit smoking since being diagnosed with cancer, relative to 22% of non-Hispanic whites.…”
Section: Discussionmentioning
confidence: 66%
“…Allison [74], however, reported a significant association with pain and employment when comparing unemployed patients with employed or retired patients. Chan et al [75] examined the medical records of 77 head and neck cancer patients, finding an association of divorced status with poorer pain. A study conducted in France and Canada on a group of oral, larynx and pharynx cancer patients [59] reported that French-speaking Canadians complained of significantly more pain than did English-speaking Canadians and French-speaking French head and neck cancer patients, even when controlled for possible socio-demographic and clinical predictors.…”
Section: Resultsmentioning
confidence: 99%